2011
DOI: 10.1007/s10512-011-9442-0
|View full text |Cite
|
Sign up to set email alerts
|

Results of U0.55Pu0.45N and U0.4Pu0.6N mixed mononitride fuel tests in a bor-60 reactor to burnup 12% h.a.

Abstract: The results of post-reactor studies of U 0.55 Pu 0.45 N and U 0.4 Pu 0.6 N mixed mononitride fuel elements (density 85% of the theoretical value) and a helium sublayer are presented. The fuel elements are irradiated in a BOR-60 reactor to burnup 9.4 and 12.1% h.a., respectively, with power density 430 and 540 W/cm. All fuel elements remained hermetic; the ChS-68 steel cladding (20% cold deformation) retained excess plasticity. The maximum zone of interaction between the cladding and the fuel and fission pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For the safe and efficient use of nitride fuels, it is therefore important to have a comprehensive understanding of their properties, including the generation and migration of fission products in the fuel matrix, especially as post-reactor studies using (U, Pu)N mixed fuel found relative yields of 19 and 19.3% of Kr and Xe, respectively, in the fuel-clad gap. 16 However, compared with UO 2 , gas release models for UN are rudimentary. There are several theoretical works on the behavior of Kr and Xe in UN, 17−20 but they are based on different methods and the results are not consistent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the safe and efficient use of nitride fuels, it is therefore important to have a comprehensive understanding of their properties, including the generation and migration of fission products in the fuel matrix, especially as post-reactor studies using (U, Pu)N mixed fuel found relative yields of 19 and 19.3% of Kr and Xe, respectively, in the fuel-clad gap. 16 However, compared with UO 2 , gas release models for UN are rudimentary. There are several theoretical works on the behavior of Kr and Xe in UN, 17−20 but they are based on different methods and the results are not consistent.…”
Section: ■ Introductionmentioning
confidence: 99%